The effect of obsessive compulsive symptoms on psychopathology in patients with schizophrenia - Ng, Boon Seng; Yee, Anne; Danaee, Mahmoud; Seng, Loh Huai; Jambunathan, Stephan Thevananthan (Universidade de Sao Paulo, 2018)
Background: There is a growing interest on the impact of comorbid obsessive-compulsive symptoms (OCS) on the course and severity of schizophrenia in recent years. Objectives: This study determined the prevalence of OCS in schizophrenia patients and the clinical outcomes of the comorbidity. Methods: A total of 220 schizophrenia patients were recruited. All the participants completed Structure Clinical Interview version, Yale Brown Obsessive Compulsive Scale, Calgary Depression Scale for Schizophrenia, Columbia Suicide Severity Rating Scale and World Health Organization Quality of Life – Brief Version (WHOQOL-BREF). Results: Significantly higher number of schizophrenia patients with OCS were taking Clozapine (p = 0.023) and antidepressants (p = 0.013). Schizophrenia patients with OCS showed more severe positive (p < 0.001) and general symptoms (p < 0.001) of schizophrenia, higher depressive symptoms (p = 0.013), higher suicidality (p < 0.001), more hospitalization (p = 0.044), poorer physical (p = 0.034) and psychological (p = 0.032) domain in WHOQOLBREF. Discussion: Schizophrenia patients with OCS are associated with more severe psychopathology and depressive symptoms which subsequently suffered poorer physical and psychological health. Hence, recognition of OCS in schizophrenia and early initiation of effective treatment may be able to reduce the burden for people with chronic mental illness.